CRISPR-Cas and Beyond: Innovative Biotechnological Techniques in Microbial Engineering - Najm, Asad Ali; Jader, Israa Shaker; Hussein, Ahmed Ali; Hussein, Yousif Karim; abd, Soror salah (American Journal of Biology and Natural Sciences, 2025)
The advancement of microbial engineering has been significantly accelerated by the development of innovative genome-editing techniques, particularly CRISPR-Cas systems. Despite the rapid evolution of genome engineering, a knowledge gap persists in fully optimizing microbial strains for industrial biotechnology, biomedicine, and environmental applications. This review systematically explores the emergence, mechanisms, and applications of CRISPR-Cas and alternative genome-editing technologies such as TALENs and ZFNs in microbial engineering. The study highlights the integration of CRISPR-Cas in optimizing metabolic pathways, developing antibiotic resistance models, and engineering probiotics and microbial communities. Findings show that these techniques have improved precision, efficiency, and scalability in gene editing, leading to enhanced production of biofuels, pharmaceuticals, and bioproducts. The results indicate that coupling CRISPR with synthetic biology, biosensors, and machine learning opens new avenues for advanced strain development and sustainable biotechnology. However, technical barriers, biosafety, and regulatory challenges remain critical issues to address for widespread and safe implementation.